2020
DOI: 10.3390/md18060294
|View full text |Cite
|
Sign up to set email alerts
|

Marine-Inspired Enzymatic Mineralization of Dairy-Derived Whey Protein Isolate (WPI) Hydrogels for Bone Tissue Regeneration

Abstract: Whey protein isolate (WPI) is a by-product from the production of cheese and Greek yoghurt comprising β-lactoglobulin (β-lg) (75%). Hydrogels can be produced from WPI solutions through heating; hydrogels can be sterilized by autoclaving. WPI hydrogels have shown cytocompatibility and ability to enhance proliferation and osteogenic differentiation of bone-forming cells. Hence, they have promise in the area of bone tissue regeneration. In contrast to commonly used ceramic minerals for bone regeneration, a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…The samples containing only WPI (WPI_0) did not influence cell viability regardless of extract dilution (Figure 10), which confirm that WPI is cyto-compatible with MG-63 cells. Similar materials based on WPI have already been tested by Plastun et al [74] on L929 fibroblasts and by Norris et al [75] on MC3TC-E1 cells. Both studies found out that WPI-based materials were not cytotoxic against different cell types.…”
Section: Cytotoxicity Evaluationmentioning
confidence: 90%
“…The samples containing only WPI (WPI_0) did not influence cell viability regardless of extract dilution (Figure 10), which confirm that WPI is cyto-compatible with MG-63 cells. Similar materials based on WPI have already been tested by Plastun et al [74] on L929 fibroblasts and by Norris et al [75] on MC3TC-E1 cells. Both studies found out that WPI-based materials were not cytotoxic against different cell types.…”
Section: Cytotoxicity Evaluationmentioning
confidence: 90%
“…Ash content ash content of a product is also related to the mineral content of an ingredient (Sulistyoningsih et al, 2019). The mineral content contained in maggot is 30.46 g/kg or 3.046% (Ahmad et al, 2022), while whey protein isolate contains 0.7% minerals (Norris et al, 2020). The higher mineral content of maggot flour resulted in the highest ash content of F3.…”
Section: Ash Contentmentioning
confidence: 99%
“…For instance, in [15], cytocompatible WPI-bioactive glass composites were produced, supporting MG-63 osteoblast cellular functioning. In [16], WPI-WPI Urease hydrogels were synthesized, demonstrating that WPI-PG hydrogels support the growth of osteosarcoma-derived MC3T3-E1 cells. Hence, such WPI-PG hydrogels may provide a medicinal route to restrict microbial infections, whilst presenting desirable mechanical properties and promoting stem-cell attachment.…”
Section: Introductionmentioning
confidence: 99%